Chemchemal, Irak: Die Arbeiten der Jahre 2012 und 2013 - van Ess, Margarete; Luciani, Marta (e-Forschungsberichte des DAI, 2023)
Archaeological investigations on the site of Chemchemal and its region were carried out in cooperation with the University of Vienna and the Sulaimaniyah Directorate of Antiquities in 2012 and 2013. Main objectives of the project are identifying all occupational phases of this major site of the Transtigris region on the Kirkuk-Sulaimaniyah road in order to understand its function and role in relation to the Mesopotamian and eastern mountainous regions and to use the material cultural sequence as reference point for classifying surface finds from the Northern Sulaimaniyah Survey.